ANALISIS STRATEGI PENGEMBANGAN BISNIS FESYEN BERKELANJUTAN DI INDONESIA - Syahfara, Awang Diaz; Yuniarinto, Agung (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
PYLLS is a fashion MSME that develops sustainability fashion concept combined with contemporary, casual, and positive vibes themes. The objective of this research is to identify the company’s business environment and to determine the appropriate strategy for its development in Indonesia. The problems of this qualitative descriptive research were analyzed using SOAR (Strengths, Opportunities, Aspirations, Results) with the 5-I approach (Initiate, Inquire, Imagine, Innovate, Inspire to Implement). The result of this research is the description of PYLLS’ business environment, which later was used to determine the appropriate strategy for the company. This study finds that the appropriate strategy is the intensive strategy which encompasses market penetration, market development, and product development, the appropriate business development technique is the economic scale enhancement. The recommended SA strategies are adding product variations and maintaining quality through quality check. SR strategies are increasing content frequency, using environmentally friendly materials, and expanding marketing using social media. OA strategies are making collaboration, seeking investors, making business proposals concerning the potentials of sustainable fashion, adding human resource, improving the system, organizational structure, and standard operational procedure. OR strategies are activating other promotions in social media, encouraging consumers to review, and developing more unique sustainable fashion products.